Analysis of Student Readiness for Blended Learning Model Implementation in Industrial Era 4.0 - Firdaus Firdaus; Rifqi Muntaqo; Eli Trisnowati (Indonesian Journal of Science and Education (IJOSE), 2020)
Information technology (IT) has provided a new means for online learning outside conventional classrooms. By using IT, blended learning is an approach that gives the best advantage from class and online learning. It is also help the higher education to improve their understanding of how students see blended learning and formulate strategies to successfully implement blended learning. The aim of this research is to examine how students' attitudes towards various aspects of learning which can influence their readiness to participate in blended learning. We provide six aspects of learning and then collect 85 students as respondent. The analysis revealed three main findings. First, the use of technology in education is not an obstacle for students. Second, the ability to follow blended learning are influenced by four things namely attitudes toward online learning, study management, online interaction, and learning flexibility. Third, attitudes toward learning in class have a negative relationship with students' readiness to participate in blended learning. The last, student attitudes towards various aspects of learning can be important in assessing students' readiness for blended learning, which is a prerequisite for the successful application of blended learning. Keywords: Blended learning, industry 4.0, student attitudes